THERMOSTABLE REFERENCE CURRENT AND VOLTAGE SOURCES FOR HIGH-LINEAR ANALOGUE-CODE-ANALOGUE SYSTEM - AZAROV, Olexiy; FIGAS, Anna (Herald of Khmelnytskyi National University. Technical sciences, 2022)
DC sources and reference voltage sources are widely used in various electronic devices: analog-to-digital and digital-to-analog converters, DC amplifiers, sample-and-hold devices, stabilized voltage sources, and others. At the same time, the accuracy and temperature characteristics of the latter largely depend on the same characteristics of direct current and voltage sources, which are subject to stringent requirements. There are quite a lot of different approaches to the construction of reference voltage and current source circuits with thermal compensation. The most famous of them - with the use of thermally compensated zener diodes operating in reverse breakdown mode. However, devices based on them have a high power consumption and low efficiency and a high level of noise, and it is difficult to implement temperature drift compensation due to a wide spread of temperature characteristics. The so-called bandgap circuits are also widely used - transistor reference voltage sources, the value of the reference voltage of which is determined by the band gap of the semiconductor. The most famous of them are Vidlar's bandgaps and Brokau's bandgaps. The specificity of all bandgap circuits is the rigid binding of the output voltage to the band gap of the semiconductor. The article proposes an alternative approach to the construction of direct current and voltage sources, which consists in the use of circuits of two-pole direct current sources. A new approach to the construction of thermally stable reference current sources based on bipolar transistors using the band gap voltage of a semiconductor and current mirrors is proposed. The principles of operation of the circuits are described and the possibility of achieving thermal compensation is proved. Computer modelling of the static characteristics of the proposed reference current sources, in particular, the temperature drift of the currents, has been carried out. A new approach to the construction of thermally stable reference voltage sources based on bipolar transistors with the use of thermally stable reference current generators is proposed. Analytical expressions are obtained that describe operation of circuits of reference voltage sources according to the proposed approach. A method for increasing the loading capacity of these reference voltage sources is proposed.
Keywords: signal conversion; weight redundancy; reference voltage; thermal stability; compensation; reference current generator